User-Centered Design and Usability Testing of an Innovative Health-Related Quality of Life Module - Nagykaldi, Z. J.; Jordan, M.; Quitoriano, J.; Ciro, C.A.; Mold, J.W. (Applied Clinical Informatics, 2014)
Objectives: Various computerized health risk appraisals (HRAs) are available, but few of them assess health-related quality of life (HRQoL) in a goal-directed framework. This study describes the user-centered development and usability testing of an innovative HRQoL module that extends a validated HRA tool in primary care settings.Methods: Systematic user-centered design, usability testing, and qualitative methods were used to develop the HRQoL module in primary care practices. Twenty two patients and 5 clinicians participated in two rounds of interactive technology think-out-loud sessions (TOLs) and semi-structured interviews (SSIs) to iteratively develop a four-step, computerized process that collects information on patient goals for meaningful life activities and current level of disability and presents a personalized and prioritized list of preventive recommendations linked to online resources.Results: Analysis of TOLs and SSIs generated 5 categories and 11 sub-categories related to facilitators and barriers to usability and human-technology interaction. The categories included: Understanding the Purpose, Usability, Perceived Value, Literacy, and Participant Motivation. Some categories were inter-connected. The technology was continually and iteratively improved between sessions until saturation of positive feedback was achieved in 4 categories (addressing motivation will require more research). Usability of all screen units of the module was improved substantially. Clinician feedback emphasized the importance of the module’s ability to translate the patient-centered HRQoL Report into actionable items for clinicians to facilitate shared decision-making. Complete integration of the HRQoL module into the existing HRA will require further development and testing.Conclusions: Systematic application of user-centered design and human factors principles in technology development and testing may significantly improve the usability and clinical value of health information systems. This more sophisticated approach helped us translate complex clinical concepts, goal-setting steps, and decision-support processes into an accepted and value-added technology.Citation: Nagykaldi ZJ; Jordan M; Quitoriano J; Ciro CA; Mold JW. User-centered design and usability testing of an innovative health-related quality of life module. Appl Clin Inf 2014; 5: 958–970http://dx.doi.org/10.4338/ACI-2014-08-RA-0067
Keywords: Health risk appraisal; user-centered design; quality of life; goal-directed care; prioritization